Implementação de protótipo de resfriador termoelétrico por efeito Peltier aplicado a dispositivos semicondutores de potência - Moraes, Thiago Finotti de (2014)
In any electrical or electronic circuit, thermal energy is a quantity that is always present and generally must be considered in the specifications of any application. In many cases, the heat from the Joule effect, as well as from other internal and irreversible losses, represent the biggest share of maximum heat that a system can dissipate under normal operation. In Power Electronics, the study and application of semiconductor power switches are particularly important. Many solutions have been developed over the years aiming to mitigate electrical losses and heat built-up in semiconductor power switches. It is important to state that the current amount of research available to academics and the general public into thermal effects on semiconductor power switches is not as wide as that concerning the applications of those switches. It is remarkably reduced the amount of work concerning active cooling of semiconductor power switches and components, as well as concerning the behavior of semiconductor power switches and components under active cooling. Thus, there is a lack of studies aiming the investigation of the behavior of electric switches under different thermal loads. Because of this lack, this work is focused on a proposal of an equipment actively cools semiconductor power switches used in Power Electronics, particularly those usually found in switched mode power supplies. The main purpose of this work is to develop an equipment for being used on a lab bench based on Peltier technology that sets thermal action on semiconductor power switches, making possible the evaluation of the behavior of these switches under different thermal exposures and temperatures. Fist, the Peltier technology was investigated and, later on, a solution was developed allowing the usage of this technology on semiconductor power switches. A detailed description and the calculations of the developed thermoelectric system are presented. The results of this work are presented as a comparative study of the behavior and limits of performance of MOSFETs in DC-DC Boost converters under active cooling compared to traditional passive heat sinks. During active cooling the MOSFET was cooled below ambient temperature, assuring its external thermal safety. The experimental results confirm the operation as intended. The main confirmed advantages were greater dissipated power, increase of thermal margin and capacity of actively transferring heat to an overloaded area to another place.